Enhancing the Teaching of English Literature Through the Utilization of Digital Storytelling : The Case of First - Year LMD - KADOUS, Mimouna; BOUMEDIENE,Houda (Faculty of Letters and Foreign Languages Department of English, 2024)
Over the years, literature has been viewed as a tool to comprehend people from other cultures and histories. It can elicit some form of feeling among the readers and it investigates the human psyche. In recent years, learning resources that include; up-todate materials like; computer digital tools applications are referred to as the best ways of passing information which is part of digital storytelling. This study intends to evaluate the effectiveness of incorporating digital storytelling as a teaching aid for literature. Therefore, it will try to determine the effectiveness of using the implementation of digital storytelling in the teaching of English short stories, a new innovative tool that will present the experiences and views of teachers and students as to how stories can be delivered to students and nurture higher students’ performance in literature subjects. This work has a descriptiveanalytical nature based on the qualitative method. The data were collected through a questionnaire addressed to First-year LMD students randomly chosen at Ammar Telidji University of Laghouat; and a semi-structured interview with five teachers of literature. The findings of the study showed that the integration of Digital Storytelling in teaching and learning English literature is beneficial, important, motivating and exposes students to better understanding of the stories and its plot as well. The fact that contributes in ameliorating their achievements in literature classes. The current study can be interpreted among the first steps in the research on digital storytelling integration. However, the results of this study should be treated with caution due to the small sample size and the lack of details regarding the participants’ views. On this basis, future research could further examine the ability of digital storytelling to facilitate both literature teaching and learning in EFL literature classes.